As narrativas populares na construção da construção da cartografia do Jd. Irene / Zona Sul de SP - Francisco, Eliana Aparecida (2019)
In addition to the statistical data, each place demonstrates a social reality that, in order to be grasped, requires careful observation and listening to the different forms of narratives that constitute the local historical process, free of prejudice, and at the same time as micro face of this reality, there is a macro interface with the wider social reality. Thus, when we analyze the social indicators and place them within the perspective of territories of inclusion or exclusion, we make it possible to construct rules for reading reality, but by using the narratives of the actors of these territories, it is possible to build a “body”, a “Face”, a web of meanings capable of giving meaning and historicity to the indicators. Given this, this research aimed to describe and study, from oral narratives, the history of the development of Jardim Irene neighborhood, located in the outskirts of the south of São Paulo and its social practices. Qualitative, the research used the cartographic method made from observations, interviews and conversation wheels with the participation of residents of the first to the third generation of the neighborhood, thus privileging the chronological and generational time of the speeches. We conclude that the narratives can present the way of being of a given place, describing the meanings of a collective doing, which from a territoriality, based on coexistence and affectivity, drives the experience that, over time, gain a character of belonging and identity